2018
DOI: 10.3390/f9060303
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Multisource Remote Sensing for Mapping the Biomass of a Degraded Amazonian Forest

Abstract: In the agricultural frontiers of Brazil, the distinction between forested and deforested lands traditionally used to map the state of the Amazon does not reflect the reality of the forest situation. A whole gradient exists for these forests, spanning from well conserved to severely degraded. For decision makers, there is an urgent need to better characterize the status of the forest resource at the regional scale. Until now, few studies have been carried out on the potential of multisource, freely accessible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…By comparing the results of the correlation analysis, the coefficients from GWR, and the attribute importance from RF, it was indicated that texture characteristics of Sentinel-1 had great potential for estimating AGB, which was also shown in previous studies [98,99]. Additionally, it was a pioneering finding that the vegetation biophysical variables of Sentinel-2 were very helpful for AGB estimation using a local regression, which was found previously by non-parametric prediction [55].…”
Section: Sentinel-derived Predictorssupporting
confidence: 70%
“…By comparing the results of the correlation analysis, the coefficients from GWR, and the attribute importance from RF, it was indicated that texture characteristics of Sentinel-1 had great potential for estimating AGB, which was also shown in previous studies [98,99]. Additionally, it was a pioneering finding that the vegetation biophysical variables of Sentinel-2 were very helpful for AGB estimation using a local regression, which was found previously by non-parametric prediction [55].…”
Section: Sentinel-derived Predictorssupporting
confidence: 70%
“…Synthetic Aperture Radar (SAR) data, such as L-band Advanced Land Observing Satellite/Phased Array L-band Synthetic Aperture Radar (ALOS/PALSAR) [19] and X-band TerraSAR-X data, are widely used in the estimation of forest biomass [20,21]. SAR is not affected by illumination and climate conditions and it can penetrate vegetation to obtain information, covering relatively large areas in a short period of time [20].At the meso-scale, many studies have demonstrated the potential of optical and radar remote sensing-derived indicators to estimate forest biomass [22,23]. However, there is a large range and many uncertainties of remote sensing.…”
mentioning
confidence: 99%
“…At the meso-scale, many studies have demonstrated the potential of optical and radar remote sensing-derived indicators to estimate forest biomass [22,23]. However, there is a large range and many uncertainties of remote sensing.…”
mentioning
confidence: 99%
“…Two field missions in May and August 2015 made it possible to build a typology of degraded forests using GPS data acquisition and qualitative descriptions (see further details in Bourgoin et al., ). Based on the spatial distribution of the data, Google Earth images and Esri World Imagery (July 2016), the plot reference database was completed by visual interpretation of disturbance impacts.…”
Section: Methodsmentioning
confidence: 99%
“…In the same area, which represents an old Amazon agricultural frontier with a mosaic of degraded forest, among a number of other variables, Bourgoin et al. () classified Landsat spectral unmixing using CLASlite and mid‐infrared variables as the most robust and most explanatory variables of the aboveground biomass remaining in degraded forest. With these advances, there is now a need to study the cumulative impacts of forest damage over time.…”
Section: Introductionmentioning
confidence: 99%